TERATOGENIC RISKS OF COSMETIC INGREDIENTS DURING PREGNANCY: REVIEW - Nisa Raudotul Auli; Briliana Suryani Kusumakinasih; Tri Dewi Zakinah; Jenifer Kolina (Institut Teknologi Sumatera, 2025)
Cosmetics are one of the necessities, especially for women to maintain healthy skin and appearance to become more confident. Cosmetics are products that are widely applied to the body, especially the skin, and their compositions come into contact with the skin for many years with the user. Therefore, the ingredients used in cosmetics must be safe and have concentrations that can be tolerated by the body, so as not to cause ongoing harmful effects. According to European law, all cosmetics approved for circulation in the European Union must be safe for users, and the responsibility for this lies with manufacturers, distributors, and importers. However, the use of cosmetics can have undesirable effects due to the presence of certain chemicals. often, these chemicals have harmful and long-lasting effects, especially for pregnant women as they can affect foetal growth and development. There are cosmetic ingredients that have been shown to be teratogenic and potentially harmful during and after pregnancy. This review explores the various teratogenic substances, their impact on pregnancy, and how to prevent the use of teratogenic cosmetic ingredients. It is acknowledged that exposure to mercury during pregnancy and childhood poses a serious risk to public health. To effectively guide future cosmetic recommendations, more studies especially examining mercury, hydroquinone, retinoic acid from cosmetics are necessary. Key words: Cosmetics, Hydroquinone, Mercury, Retinoic acid, Teratogenic.